Purveyors of the Commercial Determinants of Health Have No Place at Any Policy Table; Comment on "Towards Preventing and Managing Conflict of Interest in Nutrition Policy? An Analysis of Submissions to a Consultation on a Draft WHO Tool" - Ronald Labonté (Kerman University of Medical Sciences, 2022)
With public health attention on the commercial determinants of health showing little sign of abatement, how to manage conflicts of interest (COI) in regulatory policy discussions with corporate actors responsible for these determinants is gaining critical traction. The contribution by Ralston et al explores how COI management has itself become a terrain of contestation in their analysis of submissions on a draft World Health Organization (WHO) tool to manage COI conflicts in development of nutrition policy. The authors identify two camps in conflict with one another: a corporate side emphasizing their individual good intents and contributions, and an non-governmental organization (NGO) side maintaining inherent structural conflicts that require careful proscribing. The study concludes that the draft tool does a reasonable job in ensuring COI are avoided and policy development sheltered from corporate self-interests, introducing novel improvements in global governance for health. At the same time, the tool appears to adhere to a belief that private economic (corporate) and public good (citizen) conflicts can indeed be managed. I question this assumption and posit that public health needs to be much bolder in its critique of the nature of power, influence, and self-interests that pervade and risk dominating our stakeholder models of global governance.